Manajemen Strategi dalam Meningkatkan Pembelajaran Tahfidz Al-Qur'an di Madrasah Aliyah - Sartika, Devi; Murniyanto; Sahib, Abdul (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research aims to find out the strategies used by MA Ulul Albab to improve the learning of Tahfidz al-Qur'an. This research uses qualitative methods and data collection techniques. Observation, Interview, and documentation. The research location is at Madrasah Aliyah Ulul Albab Lubuk Linggau. The research results explain that the strategy formulation carried out by MA Ulu Albab was the formulation of a vision and mission, formulation of school goals and objectives, and planning strategies for learning Al-Qur'an Tahfidz. The strategy evaluation carried out by MA Ulu Albab is context evaluation, evaluation, input, evaluation, process, and product evaluation. Context evaluation shows that the institution has clear goals in the Tahfidz learning program, the institution also provides adequate supervising teachers, for every ten students there is one teacher who guides the input evaluation shows that the institution already knows the students' abilities with the placement test, students who want to take The takhosus program must first test its capabilities to see if it can meet the memorization targets. The process evaluation shows that the suitability of learning time is considered good because it runs according to the planned schedule.